الخط العربي - أ.د. حسن عبد العليم يوسف (Universitas Negeri Malang, 2021)
Arabic calligraphy is the art and design of writing in various languages ​​that use Arabic letters. Arabic writing is characterized by being connected, which makes it capable of acquiring different geometric shapes through extension, retrograde, rotation, angulation, interlacing, overlapping and composition. Calligraphy is associated with Arabic decoration, as it is used to decorate mosques and palaces. It is also used to sweeten manuscripts and books, especially copies of the Holy Qur’an. This field has witnessed a turnout from Muslim artists because of the Sharia's prohibition on depicting humans and animals, especially in relation to holy places and the Qur'an. This research is included in the qualitative research that uses the descriptive method. Data sources are data from books, magazines, facts and websites related to the discussion about the title. The result of this research is (1) the history of Arabic calligraphy, (2) the stages of Arabic calligraphy, (3) types of Arabic calligraphy, (4) Arabic calligraphy in Andalusia. الخط العربي هو فن وتصميم الكتابة في مختلف اللغات التي تستعمل الحروف العربية. تتميز الكتابة العربية بكونها متصلة مما يجعلها قابلة لاكتساب أشكال هندسية مختلفة من خلال المد والرجع والاستدارة والتزوية والتشابك والتداخل والتركيب. يقترن فن الخط بالزخرفة العربية حيث يستعمل لتزيين المساجد والقصور، كما أنه يستعمل في تحلية المخطوطات والكتب وخاصة نسخ القرآن الكريم. وقد شهد هذا المجال إقبالا من الفنانين المسلمين بسبب نهي الشريعة عن تصوير البشر والحيوان خاصة في ما يتصل بالأماكن المقدسة والمصاحف. يدخل هذا البحث ضمن البحث النوعي الذي يستخدم المنهج الوصفي. مصادر البيانات هي بيانات من الكتب والمجلات والوقائع والمواقع الإلكترونية ذات الصلة بالمناقشة حول العنوان. وأما النتيجة هذه البحث فهو (1) تاريخ الخط العربي ، (2) مراحل الخط العربي ، (3) أنواع الخط العربي، (4) الخط العربي في الأندلس.